The Real and the Ideal Engineer-Technologist in the View of Employers and Educators - Khairullina, Elmira R.; Makhotkina, Liliia Yu.; Kiryakova, Aida V.; Baranov, Vladimir V.; Maksimova, Olga G.; Khrisanova, Elena G.; Piralova, Olga F.; Masalimova, Alfiya R. (International Review of Management and Marketing, 2016)
In accordance with the tendencies of socio-economic development and a high need for competitive engineers-technologists in contemporary society, Russia needs such a modernization of higher professional technical education system that takes into account the requirements of modern manufacture. Therefore, this article is aimed at expert research by employers and university teachers of professional and personal qualities of a competitive engineer-technologist. The leading methods in the study of this problem are the observation, conversation, expert interviews, questionnaires and testing allowing reveal an assessment by employers and teachers of most important professional competence and personal qualities of engineers-technologists. The paper finds that the most important professional competences, communication skills and moral qualities of the ideal and the real engineer - technologist, allocated by business leaders and teachers of the university, in fact are the same. Also it reveals discrepancies in the evaluation by employers and educators of engineers'-technologists' personal qualities. The materials of this article may be useful in the selection and structuring of the content of engineers-technologists' training, and may be taken into account in the implementation of students' training and industrial practice. Keywords: real, ideal, engineer - technologist, employers, educators. JEL Classifications: A22, I 23, Z39